Blinding Orbital Apex Syndrome due to Onodi Cell Mucocele. (15th May 2014) - Fleissig, Efrat; Spierer, Oriel; Koren, Ilan; Leibovitch, Igal
Abstract : The onodi cell is a posterior ethmoidal cell that is pneumatized laterally or superiorly to the sphenoid sinus with close proximity to the optic nerve. A mucocele, a benign, expansile, cyst-like lesion of the paranasal sinuses, may uncommonly involve the onodi cell causing compression of the optic nerve and nearby structures. In this paper, we report a rare case of onodi cell mucocele causing orbital apex syndrome, with prompt recovery after endoscopic removal. However, optic neuropathy did not improve and the patient remained blind.